2002
DOI: 10.1002/polb.10250
|View full text |Cite
|
Sign up to set email alerts
|

Processing, mechanical properties, and fracture behavior of cereal protein/poly(hydroxyl ester ether) blends

Abstract: Blends of poly(hydroxy ester ether) (PHEE), a recently developed bisphenol A ether‐based synthetic biodegradable thermoplastic polymer, with a soybean protein isolate and two hydrolyzed wheat glutens were studied. Blends of the proteins with PHEE were produced from 20 to 70% by weight of protein content. Young's moduli of the protein/PHEE blends fall in the range of 0.8–1.5 GPa with tensile strengths ranging from 10 to 30 MPa. Critical stress‐intensity factors of the blends ranged from 2 to 9 MPa‐m1/2 dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…10 On the other hand, blends of SP and poly(hydroxyl ester ether) exhibited acceptable mechanical properties without using a compatibilizer, due to strong hydrogen bonding between the two components. 4 SP plasticizing conditions also showed a significant influence on the compatibility between SP and polyester. 11 Other SP plastics, such as SP/ PU, 12,13 SP/lignin, 14 and SP/chitin, 15,16 have also been studied.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…10 On the other hand, blends of SP and poly(hydroxyl ester ether) exhibited acceptable mechanical properties without using a compatibilizer, due to strong hydrogen bonding between the two components. 4 SP plasticizing conditions also showed a significant influence on the compatibility between SP and polyester. 11 Other SP plastics, such as SP/ PU, 12,13 SP/lignin, 14 and SP/chitin, 15,16 have also been studied.…”
Section: Introductionmentioning
confidence: 95%
“…However, strong intra-and intermolecular interactions of SP result in high melt viscosity that makes the melt processing, such as extrusion and injection molding, very difficult unless a sufficient amount of plasticizers and processing aids are added. [2][3][4] Although water serves as an efficient plasticizer during the melt processing of SP, it evaporates during processing and storage. The properties of the resulting products change with the humidity of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In many early studies SP was merely used as a filler to blend with other thermoplastic polymers. [18][19][20][21] Although the resulting blends showed higher water resistance, improved processability, and/or higher toughness than neat SP plastics, they often exhibited lower strength than either component of the blends. In an early study, we demonstrated that soy protein isolate (SPI) and soy protein concentrate (SPC) containing extra water could be processed as a plastic melt in blending with PLA.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, this class of materials displayed the typical biodegradability [4,5], which makes the materials a class of interesting candidates for environmentally benign materials. Due to the potential application, the investigations on the structure and properties of the polymers have begun to appear [6][7][8][9][10][11]. Most of the previous studies are concerned with the composite systems comprised of PHEE with some cereal products such as starch, protein [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%